2022
DOI: 10.1007/s11695-022-06255-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of e-Mobile Training and Consultancy Services on Bariatric Surgery Patients: A Randomized Clinical Trial

Abstract: Purpose This study was conducted as a randomized controlled trial to determine the effects of e-mobile training and consultancy services on self-care agency, body image, and quality of life in patients undergoing bariatric surgery. Material and Methods This study was conducted as a randomized controlled interventional study. The sample of the study consisted of 51 patients who met the sample selection criteria and volunteered to participate in the study in the Obesity C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Self-Care Mean Agency Scores and Body Image Scale scores has no significant increase in patients when provided with a POEI via mobile application [22].…”
Section: Quality Of Lifementioning
confidence: 90%
See 3 more Smart Citations
“…Self-Care Mean Agency Scores and Body Image Scale scores has no significant increase in patients when provided with a POEI via mobile application [22].…”
Section: Quality Of Lifementioning
confidence: 90%
“…During the second phase, full-text review narrowed the pool to 17 total studies for this systematic review. From the 17 studies that matched the inclusion criteria, 15 studies reported a statistical significance improvement in one or more patient postoperative outcomes (Table 2) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Literature Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The app of Doğan et al enabled bariatric patients to have a live consultation with researchers and contained educational materials [49]. The app did not improve self-care, quality of life and the self-body image.…”
Section: Communicationmentioning
confidence: 99%